Zedenlessen in Geschenkverpakking: Opmerkelijke Nieuwjaarspreken Uit De Zeventiende En De Achttiende Eeuw: Gift-wrapped lessons in morals: noteworthy New Year's sermons in the 17th and 18th centuries. - Storme, Hans (1993)
In the Netherlands in the 17th and 18th centuries New Year's was one of the few occasions on which the use of humor in sermons was acceptable. Drunks, foolish youngsters, and other sinners were the special targets of jokes with highly moralistic content.
Keywords: Netherlands; New Year; SERMON (Literary form); Wit & humor